Input And Output In School Of Full-Day Systems In Madrasa Ibtida'iyah Babul Hikmah Kalianda South Lampung - Hasan, Yetri; Apriawan, Nuzula (Universitas Islam Negeri Raden Intan Lampung, 2021)
To make students independent, fostering togetherness and awareness of worship Full Day School students is one program that can be an alternative to improve it. Full Day School is one of the excellent programs initiated by several schools in Indonesia. The purpose of this study was to study the input and output of a full-day school Madrasah Ibtida'iyah Babul Hikmah. The type of research used is descriptive qualitative research. With data collection techniques, namely interviews, observation, documentation and data triangulation. The results of this study indicate the full system of schools in the Madrasah Ibtida'iyah Babul Hikmah running effectively, successfully visible from the input and output in the school.